Exploring transformative learning when developing medical students' non‐technical skills. Issue 3 (20th February 2020) - Kerins, Joanne; Smith, Samantha Eve; Phillips, Emma Claire; Clarke, Benjamin; Hamilton, Ailsa Lauren; Tallentire, Victoria Ruth
Abstract: Context: Non‐technical skills (NTS) training should be incorporated into medical students' education and simulation‐based approaches are often utilised to facilitate this. Such experiences have the potential to foster transformative learning by facilitating a reassessment of one's prior assumptions and a significant shift in one's outlook, referred to as the process of perspective transformation. The aim of this research was to explore how NTS training might facilitate transformative learning in final‐year medical students. Methods: Following ethical approval, medical student volunteers from four medical schools (Aberdeen, Dundee, Edinburgh and Glasgow) participated in simulation sessions, were debriefed with an emphasis on NTS using a behavioural marker system and then took part in focus groups. Focus group discussions were semi‐structured and questions were based on the phases of perspective transformation identified by Jack Mezirow. Focus group discussions were audiorecorded, transcribed verbatim, anonymised and analysed using template analysis. Results: A total of 33 medical students took part in five focus groups. There was evidence of the following stages of perspective transformation: Phase 2 (self‐examination with emotional disturbance, including fear, anxiety, guilt, shame and frustration); Phase 3 (critical assessment of assumptions, including the undervaluing of NTS, recognising that technical skills alone are insufficient, and recognising that it is possible to improve one's NTS); Phase 5 (exploring options for new roles, relationships and actions), and Phase 6 (planning a course of action for future simulations, as a medical student and as a doctor). Conclusions: This study deepens our understanding of how exposure to NTS training in simulation‐based education influences the learning of medical students and shows that such exposure can result in the cognitive phases of transformative learning. It provides us with valuable insights into medical students' perspectives on their learning of NTS at a pivotal stage in training and represents an interesting way of assessing the educational impact of such sessions.